IJCM_171A: A community-based study on awareness of organ donation among in Arang block of Raipur district Chhattisgarh. - Jacob Sewa Vibhuti; Verma Nirmal; Jain Kamlesh; Jaiswal Prashant (Wolters Kluwer Medknow Publications, 2024)
Background: For many of the end-stage organ diseases, organ transplantation is the most preferred treatment. The need for the organ transplantation is higher than the availability. For the transplantation program to be successful, awareness regarding organ donation is needed and people must have a positive attitude toward donating organs. Objective: To determine the knowledge, attitudes, and practices regarding organ donation in Arang block of Raipur district Chhattisgarh. Methodology: Community based cross-sectional study used in this study. Simple random sampling was used to generate a sample of 100 in Arang block of Raipur district. Face to Face interview was conducted based on a semi structured questionnaire in Arang block of Raipur district. Data was taken from MS Excel sheet and analysed. Results: The majority of the study participants belongs to 44.9 year average mean with 15.4 Standard deviation. 65% of respondents were male and 35% were female. The study shows that 64% of respondents studied high school or above. Per capita income of 40% belong to Lower class 5. Majority of respondents have good knowledge and 75% have positive attitude for organ donation. Conclusion: The present study concluded there was good knowledge among the community participants. However, there questionnaire were kept distinct keeping in mind to their level of knowledge. Attitude variable didn't have much disparity.